Assessing Government Transparency: An Interpretive Framework. Issue 4 (April 2018) - Meijer, Albert; 't Hart, Paul; Worthy, Ben
How can we evaluate government transparency arrangements? While the complexity and contextuality of the values at stake defy straightforward measurement, this article provides an interpretative framework to guide and structure assessments of government transparency. In this framework, we discern criteria clusters for political transparency—democracy, the constitutional state, and social learning capacity—and for administrative transparency—economy/efficiency, integrity, and resilience. The framework provides a structured "helicopter view" of the dimensions that are relevant for a contextual assessment of transparency. An illustrative case discussion of the introduction of Freedom of Information (FOI) in the United Kingdom demonstrates its utility.